To dye or not to dye: a randomized, clinical trial of a triple dye/alcohol regime versus dry cord care - Janssen, Patricia A; Selwood, Barbara L; Dobson, Simon R; Peacock, Donlim; Thiessen, Paul N (Pediatrics (Evanston), 2003)
The use of antibacterial agents to clean and dry the stump of the newborn's umbilical cord after birth has recently been abandoned by many neonatal units in favor of dry cord care. The objective of this study was to compare cord bacterial colonization and morbidity among newborns whose cords were treated with triple dye and alcohol versus dry cord care. We randomly allocated 766 newborns to either 2 applications of triple dye to the umbilical cord stump on the day of birth with alcohol swabbing twice daily until the cord fell off (n = 384) or dry care (n = 382). Dry care consisted of spot cleaning soiled skin in the periumbilical area with soap and water, wiping it with a dry cotton swab or cloth, and allowing the area to air dry. Umbilical stumps on all subjects were swabbed and cultured. Community health nurses visiting at 2 or 3 days after hospital discharge observed the stump for signs of infection. Follow-up phone calls were made to mothers within 3 weeks of discharge. One infant in the dry care group was diagnosed with omphalitis. The umbilical stump was colonized with alpha-hemolytic streptococcus and coagulase-negative staphylococcus. Infants in the dry care group were significantly more likely to be colonized with Escherichia coli (34.2% vs 22.1%), coagulase-negative staphylococci (69.5% vs 50.5%), Staphylococcus aureus (31.3% vs 2.8%), and group B streptococci (11.7% vs 6.0%). Community health nurses were significantly more likely to observe exudate (7.4% vs 0.3%) and foul odor (2.9% vs 0.7%) among infants allocated to the dry care group during the home visit. Omphalitis remains a clinical issue. Cessation of bacteriocidal care of the umbilical stump must be accompanied by vigilant attention to the signs and symptoms of omphalitis.